Propofol allows precise quantitative arterial spin labelling functional magnetic resonance imaging in the rat - KERSKENS, CHRISTIAN; BLAU, CHRISTOPH; KELLY, MICHAEL (My University, 2010)
Functional magnetic resonance imaging (fMRI) techniques highlight cerebral vascular responses which are coupled to changes in neural activation. However, two major difficulties arise when employing these techniques in animal studies. First is the disturbance of cerebral blood flow due to anaesthesia and second is the difficulty of precise reproducible quantitative measurements. These difficulties were surmounted in the current study by using propofol and quantitative arterial spin labelling (QASL) to measure relative cerebral blood volume of labelled water (rCBVlw), mean transit time (MTT) and capillary transit time (CTT). The ASL method was applied to measure the haemodynamic response in the primary somatosensory cortex following forepaw stimulation in the rat. Following stimulation an increase in signal intensity and rCBVlw was recorded, this was accompanied by a significant decrease in MTT (1.97 ? 0.06 s to 1.44 ? 0.04 s) and CTT (1.76 ? 0.06 s to 1.39 ? 0.07 s). Two animals were scanned repeatedly on two different experimental days. Stimulation in the first animal was applied to the same forepaw during the initial and repeat scan. In the second animal stimulation was applied to different forepaws on the first and second day. The control and activated ASL signal intensities, rCBVlw on both days were almost identical in both animals. The basal MTT and CTT during the second scan were also very similar to the values obtained during the first scan. The MTT recorded from the animal that underwent stimulation to the same paw during both scanning sessions was very similar on the first and second day. In conclusion, propofol induces little physiological disturbance and holds potential for longitudinal QASL fMRI studies.
PUBLISHED
Keywords: Anaesthesiology; propofol; Nanoscience & Materials; Neuroscience; Next Generation Medical Devices